Anti-microbial activity screening of crude methanolic extracts of Acanthus ilicifolias., Clerodendrum inerme Gaertn and Ceriops tagal C. B. Rob. - Baibado, Joewel (2007.)
The antimicrobial properties of Acanthus ilicifolius, Celrodendrum enerme, and Ceriops tagalwere tested against Gram (+) bacteria (STaphylococcus aureus and Bacillus subtiles), Gram (-) bacteria Escherichia coli and Pseudomonas aeruginosa ), and the fungus (Candida albicans), a pathogenic yeast. The crude methanolic extracts of A. ilicifolius, C. inerme, and C. tagal revealed antimicrobial property. C. tagal extract had the highest antimicrobial activity on E. coli, B. subtilis and S. aureus with antimicrobial indeces of 2.11, 2.89, and 3.22 respectively. C. inerme had the least antimicrobial acitivity on B. subtilis only with antimicrobial index of 2.72. Qualitative test for the presence of secondary plant metabolites were also done to determine the possible sources of the antimicrobial activity. The resence of leucoanthocyanin and hydrolysable tannin C. tagal maybe responsible for its inhibitory effect on B. subtilis, E. coli, and S. aureus. The antimicrobial effect of A. ilicifolius on C. albicans and S. aureus maybe due to its alkaloid and hydrolysable tannin contents while the inhibitory action of C. inerme on B. subtilis maybe attributed to the presence of lakaloid, leucoanthocyanin, and hydrolisable tannin. The lowest concentration of the extracts that can inhibit the growth of the test organisms (MIC) was found to be 1000 ug/mL asshown by the presence of turbidity, whereas, the minimum concentration of the plant extracts that can stop the growth of the test organisms (MBC/MFC) was equal to 2000 ug/mL as shown by the absence of growth in the culture plates. Extracts from A. ilicifolius, C. inerme, and C. tagal at 2000 ug/mL is not toxic to brine shrimp as shown in the cytotoxicity assay. There was no significant difference between the zones of inhibition of C. tagal, C. inerme, and C. tagal, C. inerme, and A. ilicifloius on E. coli, B. subtilis, and C. albicans, respectively, as compared to the control antibiotics Amoxicillin and Nystatin at p<0.05. However, there was significant difference between the zones of inhibition of A. ilicifolius, C. tagal, and Amoxicillin on s. aureus at p<0.05. The antimicrobial acitivities of A. ilicifolius and C. tagal were significantly lower than that of Amixicillin against S. aureus (p<0.05). In general, A. ilicifolius showed antimicrobial activity against some Gram (+) bacteria and pathogenic yeast. Clerodendrum inerme has antibacterial effect on some Gram (+) while C. tagal can inhibit the growth of some Gram (+) and Gram (-) bacteria. The sutyd revealed that mangrove plant species can be sources of secondary metabolites for antimicrobial drug development.
Thesis (Graduate, Master of Science in Biology) College of Arts and Sciences, UP in the Visayas, Miag-ao, Iloilo. 2007.
Keywords: Acanthus ilicifolius -- Extracts; Clerodendrum inerme -- Extracts; Ceriops tagal -- Extracts